A system for single human supervision of multiple robots in urban search and rescue - Wong, Choon Yue. (2013)
The deployment of multiple-robots in dangerous applications like urban search and rescue (USAR) requires the robots to be supervised, possibly by only one human. This gives rise to single-human multiple-robot systems (SHMRSs). Supervising robots can increase workload and limit the supervisor’s situation awareness. Robots in a group should autonomously coordinate their actions to mitigate these issues. When designing autonomous coordination, it is important to consider the limited communication and computation resources on robots. This study has adopted a holistic approach that considers the limitations in human cognition as well as in robot communication and computation to design a solution for robot deployment in a SHMRS.